2012
DOI: 10.1017/s1365100512000247
|View full text |Cite
|
Sign up to set email alerts
|

The Case for Divisia Money Targeting

Abstract: In this paper we investigate the relationship between money growth uncertainty and the level of economic activity in the United States. We pay explicit attention to the Divisia monetary aggregates. In doing so, we use the new vintage of the data [called MSI (monetary services indices) by the St. Louis Fed], together with the simple sum monetary aggregates, over the period from 1967:1 to 2011:3. In the context of a bivariate VARMA, GARCH-in-mean, asymmetric BEKK model, we show that increased Divisia money growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…By eschewing those assumptions, the policy rule Keating and Smith (2013a) nominal GDP targeting were to be adopted. Alternatively, advocates of Friedman's preference for monetary targeting will find support for Divisia monetary targeting in Serletis and Rahman (2013). 22 Divisia monetary aggregates are not only relevant to New Keynesian models, but more relevant than commonly believed to classical real business cycle models, as found by Serletis and Gogas (2014).…”
Section: Discussionmentioning
confidence: 99%
“…By eschewing those assumptions, the policy rule Keating and Smith (2013a) nominal GDP targeting were to be adopted. Alternatively, advocates of Friedman's preference for monetary targeting will find support for Divisia monetary targeting in Serletis and Rahman (2013). 22 Divisia monetary aggregates are not only relevant to New Keynesian models, but more relevant than commonly believed to classical real business cycle models, as found by Serletis and Gogas (2014).…”
Section: Discussionmentioning
confidence: 99%
“…The results indicate stronger comovements between CPI inflation and growth in Divisia monetary aggregates than between inflation and growth rates in simple sum aggregates. Reference [12] investigate the relationship between money growth uncertainty and the level of economic activity in the United States. They use a bivariate VARMA, GARCH-in-mean, asymmetric BEKK model, and they show that increased Divisia money growth volatility is associated with a lower average growth rate of real economic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies with those data demonstrated that Divisia monetary aggregates are better measures than simple sum monetary aggregates in terms of policy criteria, such as causality and information content of the aggregate and stability of money demand equations. See, e.g., Spindt (1981, 1984), Belongia and Ireland (2006, 2015a,b,2016, Serletis and Rahman (2013), and Serletis and Gogas (2014).…”
Section: Introductionmentioning
confidence: 99%